Application Of Water As Pressure Medium In Hydraulic Hybrid System - Sabaruddin, Saiful Akmal; Yusof, Ahmad Anas; Saadun, Mohd Noor Asril; Ghazali, Rozaimi (Asian Research Publishing Network (ARPN), 2017)
Typical hydraulic hybrid system vehicles depend on oil based hydraulic fluid. Therefore, natural concerns of environment and safety promote the uses of water-based hydraulic hybrid system. The main focus of this paper is to simulate the potential of water hydraulic technology in hydraulic hybrid system vehicle. This research will include extensive study on the mathematical modeling and simulation by using Matlab/Simulink to determine the value of torque, power and efficiency of hydraulic hybrid system and diesel engines. The simulation result indicates that the resulted value of torque and efficiency verify the good combination of water-based hydraulic hybrid system in assisting diesel engine. Therefore, this novel water-based hydraulic hybrid system will reduce the usage of diesel fuel that eventually create a new green technology.